Last snow - Lustbader, Eric. (New York : Forge, 2010)
Jack McClure, Special Advisor and closest friend to the new President of the United States, takes on a personal mission along with his official one: keeping safe from harm his two incompatible companions--Annika Dementieva, a rogue Russian FSB agent, and Alli Carson, the President's daughter--and finding the people responsible for murdering an American senator who was supposedly on a political trip to the Ukraine.
Keywords: United States. -- Bureau of Alcohol, Tobacco, and Firearms -- Officials and employees -- Fiction; Young women -- Fiction; Political corruption -- Fiction; Europe, Eastern -- Fiction; Political fiction; Suspense fiction; Adventure fiction